The impact of the COVID-19 pandemic on hepatitis B virus vaccination and transmission among men who have sex with men: A mathematical modelling study. Issue 33 (5th August 2022) - Xiridou, Maria; Adam, Philippe; Meiberg, Annemarie; Visser, Maartje; Matser, Amy; de Wit, John; Op de Coul, Eline
Highlights: COVID-19-related changes in HBV vaccination can lead to more HBV infections. Despite reduced sexual activity, there may be a small increase in HBV incidence. HBV vaccination uptake must exceed pre-pandemic level to control HBV transmission. Abstract: Background: During the COVID-19 pandemic, the number of hepatitis B virus (HBV) vaccinations among men who have sex with men (MSM) has been considerably lower than before the pandemic. Moreover, less frequent HBV testing and a reduction in numbers of sex partners have been reported. We assessed the impact of these COVID-19-related changes on HBV transmission among MSM in the Netherlands. Methods: We estimated the changes in sexual activity, HBV testing, and HBV vaccination among MSM during the pandemic from Dutch data. We used a deterministic compartmental model and investigated scenarios with small or large declines in sexual activity, testing, and vaccination for the current phase of the pandemic (without available data). We examined the increase in HBV vaccinations needed to prevent further increase in HBV incidence. Results: With a decrease in numbers of sex partners of 15–25% during the first lockdown and 5% during the second lockdown, we found a decline of 6.6% in HBV incidence in 2020, despite a >70% reduction in HBV testing and vaccination during the first lockdown. With numbers of sex partners rebounding close to pre-pandemic level in 2021, and a reduction of 15% in testing and 30% in vaccination in 2021, we found an increase of 1.4% in incidence in 2021 and 3.1% in 2026. With these changes, an increase of ≥60% in HBV vaccinations in 2022 would be needed to bring the HBV incidence in 2023 back to the level that it would have had if the COVID-19-related changes had not occurred. Conclusions: Despite reductions in sexual activity during the COVID-19 pandemic, the decrease in HBV vaccinations may result in a small increase in HBV incidence after 2021, which may persist for years. It is important to restore the vaccination level and limit further increase in HBV transmission among MSM.